Nutrigenomics and proteomics in health and disease : food factors and gene interactions - Mine, Yoshinori; Miyashita, Kazuo; Shahidi, Fereidoon, 1951- (New York, NY : Wiley-Blackwell, 2009)
Includes bibliographical references and index